2018
DOI: 10.1007/s11266-018-00056-6
|View full text |Cite|
|
Sign up to set email alerts
|

Blurring the Lines Between Civil Society, Volunteering and Social Movements. A Reflection on Redrawing Boundaries Inspired by the Spanish Case

Abstract: Citizen participation is manifested through various concepts, such as activism, social movements, volunteering or civil society. The different ways of understanding popular engagement are often separated by delimitations that define them, particularly volunteering and civic action, as two highly differentiated forms of participation in the distinct academic disciplines: political science, volunteering studies, social movement studies or civil society theory. This article considers whether this basic theoretica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
0
7
0
1
Order By: Relevance
“…The decade of the 1990s without social movements all over the globe can be accounted to burgeoning civil society organizations, while the globally emerging new generation of movements from the beginning of the 2000s to the failure of civil society addressed deep structural injustices caused by global neoliberalism (Tarrow, 2011, xv). The observations made by Della Porta (2020) and others (Daniel and Neubert, 2019;Feenstra, 2018;Gready and Robins, 2017) have confirmed the transformation of associative action into collective action with a new crisis in the past two decades. Failing to capture it as a qualitative change, they depict it as exchanges of repertoire between civil society organizations and social movements or hybridization.…”
Section: Differentiating Between Associative Solidarity and Collective Solidaritymentioning
confidence: 70%
See 1 more Smart Citation
“…The decade of the 1990s without social movements all over the globe can be accounted to burgeoning civil society organizations, while the globally emerging new generation of movements from the beginning of the 2000s to the failure of civil society addressed deep structural injustices caused by global neoliberalism (Tarrow, 2011, xv). The observations made by Della Porta (2020) and others (Daniel and Neubert, 2019;Feenstra, 2018;Gready and Robins, 2017) have confirmed the transformation of associative action into collective action with a new crisis in the past two decades. Failing to capture it as a qualitative change, they depict it as exchanges of repertoire between civil society organizations and social movements or hybridization.…”
Section: Differentiating Between Associative Solidarity and Collective Solidaritymentioning
confidence: 70%
“…Gready and Robins (2017) have observed that qualitatively "new" civil society deployed more of social movements' repertoire of action, which is perfectly in line with Della Porta's observation. Confirming both, Feenstra (2018) has highlighted the tendencies of blurring boundaries between voluntarism and civic action-two forms of citizen participation attributed to civil society and social movements, respectively. Daniel and Neubert (2019) have reported similar findings regarding the blurring lines between civil society and social movements in the African context.…”
Section: Literature Reviewmentioning
confidence: 91%
“…Although TSOs too are undergoing changes that increase bureaucratic work among social workers due to partial privatization (Abramovitz & Zelnick, 2018 ), studies have shown that the level of investment and sense of efficacy among TSO social workers is higher than in GSOs (Auerbach et al, 2010 ; Freund & Tzriker, 2016 ). As TSO values are known to emphasize social ideologies and activities (e.g., citizen participation) (Freenstra, 2018 ), their organizational activities may be publicly perceived as more ‘legitimate’ (McMullin & Skelcher, 2018 ), contributing to the notion that TSO social workers have a better reputation (Freund, 2005 ; Suh, 2018 ). In turn, this notion may strengthen the social exchange between TSO social workers and their employers.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of differences between social workers in TSOs and FPOs with regard to social exchange might be related to boundary-blurring inherent in the hybridity concept (Freenstra, 2018 ). Following privatization and decentralization processes enabling transfer of values from one sector to another (Bryson et al, 2006 ), market logic (reflected in marketization of welfare services, managerialism, efficiency, and value for money) became assimilated within GSO tenders (Abramovitz & Zelnick, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Es una democracia joven después de una dictadura , y una transición política (1975)(1976)(1977)(1978) que se ha consolidado tras una legalización de determinadas fuerzas políticas de izquierda y un débil asociacionismo frente a otros países europeos, además de una dilatada consolidación de formas de participación no electorales con algunos momentos de una fuerte movilización ciudadana. Destacan las protestas contrarias a la integración de España en las estructuras de la OTAN, en contra de la Guerra de Irak y las derivadas de los atentados de Atocha (11M) (Feenstra 2018). Los trabajos señalan que a partir de la crisis económica y de valores de 2008, los jóvenes españoles se relacionan con la política de forma diferente.…”
Section: Introductionunclassified